Examining the impact of social media on youth vaping behavior in China: an analysis of the mediating role of perceptions of policy enforcement - Wang, Tong-Chen Lucas; Zhang, Mei-Juan; Zhang, Hualin (Frontiers in Public Health, 2025)
IntroductionResearch has established that exposure to media and the perceived enforcement of policies can influence outcomes related to (un)healthy behaviors. However, little is known about the underlying processes that may mediate the relationship. The Knowledge-Attitude-Practice (KAP) model serves as an important framework for examining health cognition and behavior change. It asserts that knowledge underpins beliefs, attitudes drive motivation, and practices reflect behaviors. In the realm of e-cigarette cessation, this study investigates the influence of media exposure on perceptions of policy enforcement, which in turn affects risk-benefit evaluations and behavioral outcomes.MethodsData for this study were collected in 2024 from an online questionnaire survey (N = 724) conducted in Guangdong China, with participants aged 18 to 30. We primarily employ methods such as mediating effect testing and regression analysis to conduct our data analysis.ResultsThe findings suggest that social media exposure, perceived policy enforcement, and perceptions of risks and benefits collectively influence youth vaping behaviors through various mediating pathways. Specifically, the results indicate that exposure to social media has a positive effect on the perceived enforcement of tobacco control policy. This perception, in turn, positively affects both risk and benefit perceptions, thereby either decreasing the likelihood of vaping through heightened perceived risks or increasing it through enhanced perceived benefits.DiscussionThe study highlights the impact of social media content concerning e-cigarettes, noting that both ambiguous advertising and health education materials can enhance the perceived enforcement of tobacco control policy. Furthermore, we investigate the impact of information shared across various social media platforms on vaping behaviors and perceptions of tobacco control policy enforcement. Implications and limitations are discussed.